Targeting ALK in Neuroendocrine Tumors of the Lung - Akhoundova, Dilara; Haberecker, Martina; Fritsch, Ralph; Höller, Sylvia; Kiessling, Michael K.; Rechsteiner, Markus; Rüschoff, Jan H.; Curioni-Fontecedro, Alessandra (Frontiers in Oncology, 2022)
Background: Anaplastic lymphoma kinase (ALK) rearrangements are known oncogenic drivers in non-small cell lung cancer (NSCLC). Few case reports described the occurrence of such rearrangements in large cell neuroendocrine carcinomas (LCNEC) of the lung without information on clinical responses to ALK tyrosine kinase inhibitors (TKIs) in these cases. Currently, neuroendocrine tumors of the lungs are not screened for ALK rearrangements. Methods: We analyzed 439 tumor biopsies from patients with neuroendocrine tumors of the lung including LCNEC (n=64), small cell lung cancer (SCLC) (n=206), typical (n=91) and atypical (n=69) carcinoids and mixed histology (n=9) for the presence of ALK rearrangements using a sequential diagnostic algorithm. ALK immunohistochemistry (IHC) was evaluable in 365 cases; fluorescence in situ hybridization (FISH) was evaluable in 30 out of the 38 IHC-positive cases, followed by next-generation sequencing (NGS), available in 15 cases. Moreover, we report disease course in three patients with ALK rearranged metastatic LCNEC, as well as treatment response to ALK TKIs. Results: Within the analyzed cohort, ALK IHC was positive in 38 out of 365 (10.4%) evaluable samples. FISH resulted positive in 5 out of the 38 (13.2%) cases: of these, 2 with atypical carcinoids and 3 with LCNEC. NGS confirmed the presence of an ALK genomic rearrangement in the 3 FISH-positive cases (2 LCNEC and 1 atypical carcinoid) where material was sufficient for sequencing, as well as in one additional LCNEC case. Two out of three patients with metastatic ALK-rearranged LCNEC received upfront treatment with the ALK TKI alectinib, and showed rapid tumor response at all metastatic sites, including multiple brain metastases. Conclusions: ALK rearrangements represent rare but targetable oncogenic driver alterations in LCNEC. Contrarily to non-small cell lung cancer, the detection of ALK rearrangements in neuroendocrine tumors of the lung is challenging since ALK IHC can lead to false positive results, and therefore needs confirmation by FISH or NGS. Upfront comprehensive molecular profiling with NGS should be performed in metastatic LCNEC in order not to miss actionable genomic alterations.